University–community engagement in the Netherlands: blurring the lines between personal values, societal expectations, and marketing - Koekkoek, Anouk; Kleinhans, Reinout; van Ham, Maarten (Frontiers in Education, 2024)
As a growing number of Dutch higher education institutions become increasingly interested and active in university-community engagement, questions have arisen about their motivations, goals, and activities in this area. This paper aims to provide insight into the factors driving universities' community engagement and how this is manifested in the Netherlands, considering, in particular, the role of marketization and corporate social responsibility. It thus offers an empirical foundation for understanding university-community engagement. Semi-structured interviews were conducted with major stakeholders in university-community engagement at four Dutch universities, including members of the executive boards. It was found that universitycommunity engagement shows several similarities to corporate social responsibility and is based on a complex mix of value-driven, performance-driven, and reaction-driven motivations. Three relationships between marketization and university-community engagement are identified, characterizing university-community engagement as a counteraction against marketization, an expression of marketization, and a result of marketization.